(3CMcGe GdEeGeI GdYXeis - (3YHO GdbGOQ Hf Ydj Hf jhSa Hf eMeO GdeZQHj GdaGSj, GdeGdcj,J (B1091 (3g` s
(3ChdgG (B:s
(3GYde Cf eHGMK GdEeGeI djS ef GdYbdjGJ s
(3BNQgG (B:s
(3hcGf jbhd GdNTHGJ GdShO GdeYdbI adf GfhGHge s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(383 (3c(B) s
Keywords: (3CUhd Gdabgs